On equality and justice principles in criminal law and the specifics of modern criminal lawmaking in the light of the exclusion of paragraph “o” from Part 1 of Article 63 of the Criminal Code of the Russian Federation - Karavaeva Yu.S. (Пенитенциарная наука, 2023)
Introduction: the amended list of aggravating circumstances published in 2010 and 2023 in connection with the addition and exclusion of paragraph “o” of Part 1 of Article 63 of the Criminal Code of the Russian Federation (“commission of an intentional crime by an employee of the internal affairs body) are of interest in the light of the principles of equality of citizens before the law (Article 4 of the Criminal Code of the Russian Federation) and justice (Article 6 of the Criminal Code of the Russian Federation), as well as in terms of modern criminal lawmaking. Purpose: taking into account the current legislation and doctrine, to determine correlation of these changes with the stated principles, as well as to indicate legislative activity trends. Methods: formal-logical and analytical methods, statistical method and interpretation method. Results: the analysis of the current constitutional and criminal legislation in terms of provisions enshrining the principles of equality of citizens before the law and justice, as well as their doctrinal and judicial interpretations, shows that the recognition of the fact of committing an intentional crime by an employee of the internal affairs body as an aggravating circumstance contradicts these principles, since it puts this category of citizens in a more vulnerable position relative to other employees of the internal affairs body whose status actually has criminality as well. In addition, the 2010 and 2023 amendments to Part 1 of Article 63 of the Criminal Code of the Russian Federation confirm the relevance of a number of trends inherent in modern criminal lawmaking. Conclusion: it seems more logical to correct the violation committed in 2010 by proposing the following wording of paragraph “o” of Part 1 of Article 63 of the Criminal Code of the Russian Federation: “commission of an intentional crime by a law enforcement officer”. Having considered the situation of the introduction of paragraph “o” in Part 1 of Article 63 of the Criminal Code of the Russian Federation in 2010 and its exclusion in 2023, the author has come to a conclusion about the existence of negative trends in criminal lawmaking, such as its opportunism, criminological unreasonableness, priority of specialization and casuistry of the criminal law as a consequence, as well as absence of an ambiguously formulated position of the higher courts in the discussion of draft laws.